2002
DOI: 10.1111/0272-4332.00061
|View full text |Cite
|
Sign up to set email alerts
|

An Exposure Assessment for Methylmercury from Seafood for Consumers in the United States

Abstract: An exposure model was developed to relate seafood consumption to levels of methylmercury (reported as mercury) in blood and hair in the U.S. population, and two subpopulations defined as children aged 2-5 and women aged 18-45. Seafood consumption was initially modeled using short-term (three-day) U.S.-consumption surveys that recorded the amount of fish eaten per meal. Since longer exposure periods include more eaters with a lower daily mean intake, the consumption distribution was adjusted by broadening the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 10 publications
4
66
0
Order By: Relevance
“…A great deal of publications on marine fish report only Hg levels because this metal is of particular concern for human health (e.g. Carrington and Bolger, 2002;Marcotrigiano and Storelli, 2003;Gochfeld, 2004, 2005;Rasmussen et al, 2006). Inorganic mercury occurring naturally or from pollution is converted to methyl-mercury (MeHg) by microorganisms and is biomagnified up the food chain.…”
Section: Comparison With Other Oceans and Guidelinesmentioning
confidence: 99%
“…A great deal of publications on marine fish report only Hg levels because this metal is of particular concern for human health (e.g. Carrington and Bolger, 2002;Marcotrigiano and Storelli, 2003;Gochfeld, 2004, 2005;Rasmussen et al, 2006). Inorganic mercury occurring naturally or from pollution is converted to methyl-mercury (MeHg) by microorganisms and is biomagnified up the food chain.…”
Section: Comparison With Other Oceans and Guidelinesmentioning
confidence: 99%
“…For example, in the case of a long half-life chemical such as methylmercury, it has been illustrated that by merging fish consumption surveys, dietary intake models, and national fish methylmercury data, reasonable agreement between biomarkers and data can be reached (Carrington and Bolger, 2002).…”
Section: Results For Case Studymentioning
confidence: 99%
“…28 Average Exposures to MeHg. At a consumption-weighted average MeHg concentration in fish of 0.15 ppm, 22 a consumption rate of 19 g/day, and a median body weight of 71.4 kg, 4,5 the corresponding population-average MeHg exposure rate would be ϳ0.039 g/kg/day, which is below the EPA-recommended limit of 0.1 g/kg/day. This estimate is also consistent with the data of Stern et al…”
Section: Fish Consumption and Mehg Exposure Fish Consumption Rates Inmentioning
confidence: 93%
“…These rates are consistent with a previous analysis. 4,5 However, although a recent survey indicated that 87.5% of the U.S. population eats fish at least once over the course of a year, 22 older data 23 suggest that in the early 1970s, 40 -50% of the population reported eating fish "seldom or never", which would increase the effective rate of consumption by "users" to ϳ27 g/day at that time. These estimates are also reasonably consistent with those of Stern et al 24 for New Jersey; their data indicate a mean portion size of 168 g and a median consumption rate of ϳ1.3 meals/week, yielding a median per capita consumption rate of ϳ30 g/day.…”
Section: Fish Consumption and Mehg Exposure Fish Consumption Rates Inmentioning
confidence: 99%
See 1 more Smart Citation